Subclinical cardiopulmonary dysfunction in stage 3 chronic kidney disease. Issue 1 (24th February 2016) - Nelson, Alexander; Otto, James; Whittle, John; Stephens, Robert C M; Martin, Daniel S; Prowle, John R; Ackland, Gareth L
Abstract : Objective: Reduced exercise capacity is well documented in end-stage chronic kidney disease (CKD), preceded by changes in cardiac morphology in CKD stage 3. However, it is unknown whether subclinical cardiopulmonary dysfunction occurs in CKD stage 3 independently of heart failure. Methods: Prospective observational cross-sectional study of exercise capacity assessed by cardiopulmonary exercise testing in 993 preoperative patients. Primary outcome was peak oxygen consumption (VO2peak ). Anaerobic threshold (AT), oxygen pulse and exercise-evoked measures of autonomic function were analysed, controlling for CKD stage 3, age, gender, diabetes mellitus and hypertension. Results: CKD stage 3 was present in 93/993 (9.97%) patients. Diabetes mellitus (RR 2.49 (95% CI 1.59 to 3.89); p<0.001), and hypertension (RR 3.20 (95% CI 2.04 to 5.03); p<0.001)) were more common in CKD stage 3. Cardiac failure (RR 0.83 (95% CI 0.30 to 2.24); p=0.70) and ischaemic heart disease (RR 1.40 (95% CI 0.97 to 2.02); p=0.09) were not more common in CKD stage 3. Patients with CKD stage 3 had lower predicted VO2peak (mean difference: 6% (95% CI 1% to 11%); p=0.02), lower peak heart rate (mean difference:9 bpm (95% CI 3 to 14); p=0.03)), lower AT (mean difference: 1.1 mL/min/kg (95% CI 0.4 to 1.7); p<0.001) and impaired heart rate recovery (mean difference: 4 bpm (95% CI 1 to 7); p<0.001)). Conclusions: Subclinical cardiopulmonary dysfunction in CKD stage 3 is common. This study suggests that maladaptive cardiovascular/autonomic dysfunction may be established in CKD stage 3, preceding pathophysiology reported in end-stage CKD.